Canada. Significant achievements 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The main activities carried out by the Institute in Canada during 2018 are identified, with respect to the needs and interests of the country, strengthening issues such as sustainable agriculture, bioeconomy, waste management, resilience against climate change, agricultural health, food safety, use of fertilizers and organic agriculture. Likewise, work was done on the management of forest resources, on improving the value chains of avocado and livestock production, especially goats, and on the genetic improvement of small ruminants. Finalmente, se apoyó en el empleo de invernaderos, de nuevas metodologías y de herramientas geoespaciales.